2020
DOI: 10.2147/prbm.s257201
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exploring Role of Personal Sense of Power in Facilitation of Employee Creativity: A Dual Mediation Model Based on the Derivative View of Self-Determination Theory</p>

Abstract: Purpose: Employee creativity is a key factor that helps organizations to gain competitive advantages. The aim of this study is to add to the knowledge of the antecedents of employee creativity. Based on the derivative view of self-determination theory, we analyzed how personal sense of power affects employee creativity, and the mediating role of affective commitment and creative self-efficacy. Participants and Methods: The participants in this study were 227 on-the-job MBA students (120 males and 107 females, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 76 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…Besides, the previous study has proved a connection between positive emotion and the flexibility of the flow of information, which increases the likelihood of idea generation (Rooij et al, 2015; Zhou & He, 2020). Therefore, positive cognition may empower and encourage benign envier, which benefits cognitive flexibility, set-breaking, and abstract thinking (Zhou & He, 2020), thus promotes idea generation.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 97%
See 4 more Smart Citations
“…Besides, the previous study has proved a connection between positive emotion and the flexibility of the flow of information, which increases the likelihood of idea generation (Rooij et al, 2015; Zhou & He, 2020). Therefore, positive cognition may empower and encourage benign envier, which benefits cognitive flexibility, set-breaking, and abstract thinking (Zhou & He, 2020), thus promotes idea generation.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 97%
“…Previous studies have also shown a connection between emotions like joy and increased investment and engagement (Zhou & He, 2020). Since benign envy motivates selfimprove behaviors, it may ensure sufficient cognitive and motivational resources to enable creative activity (Zhou & He, 2020). Therefore, the hypothesis is put forwarded as following:…”
Section: Envy and Team Creativitymentioning
confidence: 99%
See 3 more Smart Citations